A ceramic matrix composite / superalloy dissimilar joint and method of welding thereof

CN122956051APending Publication Date: 2026-10-23HARBIN INST OF TECH +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611384313.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-08
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

[0003]本发明旨在解决钎料体系的面心立方结构在高温熔融状态下诱发陶瓷基复合材料分解使焊缝区域形成脆性硅化物或金属间化合物的问题

Benefits of technology

[0015]本发明的一种陶瓷基复合材料/高温合金异质接头及其焊接方法的有益效果是:通过在陶瓷基复合材料表面预制牺牲层,并利用其在焊接过程中定向吸引FCC基活性钎料中的Ti、V或Cr活性元素并与活性钎料中的活性元素原位反应,利用牺牲层与FCC基活性元素之间的强反应性,实现牺牲层的原位转变,转变为阻隔层,阻隔层紧密、致密地附着在CMC表面,从源头抑制CMC过度分解与有害硅化物生成,避免硅化物进入焊缝并形成脆性硅化物或金属间化合物,有效抑制了陶瓷基复合材料的分解和脆性相的生成,使得焊缝中仅残留完整的面心立方塑性结构,从而在陶瓷基复合材料与高温合金的异质连接中构建了全塑性焊缝界面。由此,成功解决了传统连接中“反应控制—应力缓解”难以兼顾的矛盾,实现了高强度、高热稳定、高密封的陶瓷基复合材料/高温合金异质接头。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122956051A_ABST
    Figure CN122956051A_ABST
Patent Text Reader

Abstract

The application provides a ceramic matrix composite / high-temperature alloy heterogeneous joint and a welding method thereof, and relates to the technical field of material connection. The welding method of the ceramic matrix composite / high-temperature alloy heterogeneous joint comprises the following steps: preparing a carbon coating or a boron coating on a welding surface of a ceramic matrix composite; transforming the carbon coating or the boron coating into a carbon sacrificial layer or a boron sacrificial layer through vacuum heat treatment or annealing treatment; taking an active filler metal with a face-centered cubic structure as a matrix and adding active elements Ti, V or Cr; assembling the ceramic matrix composite, the active filler metal and the high-temperature alloy in a sandwich structure, vacuum welding, and orienting and attracting the active elements by the carbon sacrificial layer or the boron sacrificial layer and reacting the active elements with the carbon sacrificial layer or the boron sacrificial layer, so that the carbon sacrificial layer or the boron sacrificial layer is transformed into a carbon barrier layer or a boron barrier layer in situ, the welding seam only retains the face-centered cubic structure, a full-plasticity welding seam interface is constructed, and the ceramic matrix composite / high-temperature alloy heterogeneous joint is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of material joining technology, and more specifically, to a ceramic matrix composite / high-temperature alloy heterojunction and its welding method. Background Technology

[0002] Ceramic matrix composites (CMCs) have demonstrated significant application value in critical structures of aero-engine hot-end components, such as tail nozzles, due to their low density, excellent high-temperature stability, and thermal shock resistance. In engineering practice, reliable connections between CMCs and high-temperature alloy structural components have become an unavoidable technical requirement, especially for typical materials such as cobalt-based high-temperature alloys like GH5188. Compared to mechanical joining methods, brazing offers significant advantages in connection efficiency, airtightness, and precision joining of complex geometries, and is considered a feasible technical path to achieve high-strength, high-thermal-stability, and high-sealing heterogeneous joints. However, the heterogeneous joining of CMCs and high-temperature alloys has long faced a fundamental contradiction: the difficulty in synergistically controlling reaction and alleviating stress. To mitigate residual thermal stress caused by the mismatch in thermal expansion coefficients, brazing filler metal systems typically require the introduction of face-centered cubic structural elements with high melting points and excellent plasticity as the matrix, such as copper, nickel, or cobalt. However, in active brazing processes containing reactive elements (such as titanium), these face-centered cubic matrix elements readily induce the decomposition of ceramic matrix composites in their high-temperature molten state. This causes silicon to be released and diffuse into the weld area, leading to the formation of brittle silicides or intermetallic compounds. The formation of such brittle phases not only significantly weakens the mechanical strength of the joint but also severely impairs its high-temperature service stability. Even the face-centered cubic high-entropy brazing filler metal systems that have received considerable attention in recent years, such as copper-based, copper-nickel-based, cobalt-chromium-iron-nickel-manganese-based, or nickel-based brazing filler metals, cannot completely prevent the formation of intermetallic compounds, resulting in the weld failing to achieve the expected plastic deformation capacity to effectively alleviate joint stress. Summary of the Invention

[0003] The present invention aims to solve the problem that the face-centered cubic structure of the brazing filler metal system induces the decomposition of ceramic matrix composites under high temperature molten state, resulting in the formation of brittle silicides or intermetallic compounds in the weld area.

[0004] To address the above problems, this invention provides a ceramic matrix composite / high-temperature alloy heterojunction and its welding method.

[0005] In a first aspect, the present invention provides a welding method for a ceramic matrix composite / high-temperature alloy dissimilar joint, comprising the following steps: S1: A carbon or boron coating is pre-formed on the welding surface of a ceramic matrix composite material, and the carbon or boron coating is transformed into a carbon sacrificial layer or a boron sacrificial layer through vacuum heat treatment or annealing. S2: Take an active solder with a face-centered cubic structure as the matrix and add active elements Ti, V or Cr; S3: Assemble ceramic matrix composites, active brazing filler metal, and high-temperature alloys in a sandwich structure, and vacuum weld them. The carbon or boron sacrificial layer directionally attracts and reacts with the active elements, realizing the in-situ transformation of the carbon or boron sacrificial layer into a carbon or boron barrier layer. This allows the weld to retain only a face-centered cubic structure, constructing a fully plastic weld interface and obtaining a ceramic matrix composite / high-temperature alloy heterojunction.

[0006] Optionally, S1 includes: dissolving phenolic resin in acetone to prepare a phenolic resin organic solution, placing the ceramic matrix composite material in the phenolic resin organic solution for vacuum impregnation, and curing it in an air atmosphere to achieve a pre-coated carbon layer on the welding surface of the ceramic matrix composite material.

[0007] Optionally, S1 includes: dissolving dopamine powder in alcohol to prepare a dopamine organic solution, spin-coating the dopamine organic solution onto the welding surface of the ceramic matrix composite material, and vacuum drying and curing to achieve a pre-coated carbon layer on the welding surface of the ceramic matrix composite material.

[0008] Optionally, S1 includes: performing vacuum heat treatment on the carbon coating at 800°C to 1100°C for more than 10 minutes in a vacuum environment, so that the carbon coating is transformed into a carbon sacrificial layer.

[0009] Optionally, S1 includes: performing radio frequency magnetron sputtering on the welding surface of the ceramic matrix composite material using a boron target under an inert gas atmosphere to sputter and deposit a boron coating on the welding surface of the ceramic matrix composite material, the thickness of the boron coating being 100 nm to 1 μm.

[0010] Optionally, S1 includes: annealing the boron coating at 150°C to 300°C for 0.5 h to 2 h in a vacuum or inert atmosphere to transform the boron coating into a boron sacrificial layer.

[0011] Optionally, in S2, the proportion of active elements in the active solder does not exceed 20 at.%, and the active solder components are prepared by vacuum arc melting with a melting vacuum of 1×10⁻⁶. -3 Pa to 1×10 -2 Pa, melting current is 450 A to 500 A.

[0012] Optionally, S3 includes: mixing active solder with a particle size D50 of 5 μm to 30 μm with terpineol to form a solder slurry; degassing the solder slurry under vacuum; coating it onto the welding surface of the ceramic matrix composite material by scraping or screen printing; drying it under vacuum conditions of 50°C to 80°C and -0.08 MPa to -0.095 MPa for 2 h to 8 h to remove terpineol; and drying to form a solder interlayer of 50 μm to 300 μm.

[0013] Optionally, S3 includes: heating to the welding temperature range at a heating rate of 3 ℃ / min to 8 ℃ / min and holding at that temperature for 10 min to 30 min to perform vacuum welding, wherein the welding temperature range is the melting point temperature of the active brazing filler metal plus 50 ℃ to 200 ℃.

[0014] Secondly, the present invention provides a ceramic matrix composite / high-temperature alloy heterojunction, which is manufactured using the welding method for ceramic matrix composite / high-temperature alloy heterojunction as described above.

[0015] The beneficial effects of the ceramic matrix composite / high-temperature alloy heterojunction and its welding method of the present invention are as follows: By prefabricating a sacrificial layer on the surface of the ceramic matrix composite material, and utilizing the sacrificial layer to directionally attract Ti, V, or Cr active elements in the FCC-based active solder during the welding process, and reacting with the active elements in the active solder in situ, the sacrificial layer is transformed into a barrier layer by utilizing the strong reactivity between the sacrificial layer and the FCC-based active elements. The barrier layer is tightly and densely attached to the CMC surface, inhibiting the excessive decomposition of CMC and the formation of harmful silicides from the source, preventing silicides from entering the weld and forming brittle silicides or intermetallic compounds, effectively inhibiting the decomposition of the ceramic matrix composite material and the formation of brittle phases, so that only a complete face-centered cubic plastic structure remains in the weld, thus constructing a fully plastic weld interface in the heterojunction of ceramic matrix composite material and high-temperature alloy. Therefore, the contradiction of "reaction control - stress relief" in traditional joints is successfully solved, achieving a high-strength, high-thermal-stability, and high-sealing ceramic matrix composite / high-temperature alloy heterojunction. Attached Figure Description

[0016] Figure 1 This is a schematic flowchart of the welding method for a ceramic matrix composite / high-temperature alloy heterojunction according to an embodiment of the present invention. Figure 2 SEM image of the GH5188 / CMC heterojunction in Example 1; Figure 3 SEM image of the GH5188 / CMC heterojunction in Comparative Example 1; Figure 4 A bar graph showing the strength of GH5188 / CMC heterojunctions prepared with different PF mass fractions in Example 2; Figure 5 A bar graph showing the strength of GH5188 / CMC heterojunctions prepared at different brazing temperatures in Example 3. Detailed Implementation

[0017] To make the above-mentioned objects, features, and advantages of the present invention more apparent and understandable, specific embodiments of the present invention will be described in detail below with reference to the accompanying drawings. Although some embodiments of the present invention are shown in the drawings, it should be understood that the present invention can be implemented in various forms and should not be construed as limited to the embodiments set forth herein. Rather, these embodiments are provided to provide a more thorough and complete understanding of the present invention. It should be understood that the accompanying drawings and embodiments of the present invention are for illustrative purposes only and are not intended to limit the scope of protection of the present invention.

[0018] Unless otherwise defined, all technical and scientific terms used in this invention have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The terminology used in this invention's description is for the purpose of describing particular embodiments only and is not intended to be limiting of the invention. As used herein, the term "comprising" and its variations are open-ended, meaning "including but not limited to"; the term "based on" means "at least partially based on"; the term "one embodiment" means "at least one embodiment"; the term "another embodiment" means "at least one additional embodiment"; the term "some embodiments" means "at least some embodiments"; and the term "optionally" means "optional embodiments". Definitions of other terms will be given in the description below. In the description of this application, unless otherwise stated, "a plurality of" means two or more.

[0019] In related technologies, interface control strategies mainly focus on two aspects: First, optimizing interface reactions and microstructure evolution by finely adjusting process parameters such as brazing temperature and holding time. However, this method is limited by a narrow process window, making it difficult to fundamentally eliminate contradictions, and it has stringent requirements for operational repeatability. Second, introducing refractory dispersed phases into the brazing filler metal or using an intermediate layer for composite treatment in order to refine brittle phases or provide physical barriers. However, adding a second phase is difficult to form a continuous and uniform covering layer on the surface of ceramic matrix composites, and its effect on inhibiting material decomposition and metallization is limited. In addition, if barrier layers are directly prepared on the surface of ceramic matrix composites using methods such as magnetron sputtering or precursor pyrolysis, there are generally problems of insufficient interlayer bonding and easy interface delamination, which cannot meet the requirements of high-reliability bonding.

[0020] To address the problems existing in the aforementioned related technologies, embodiments of the present invention provide a ceramic matrix composite / high-temperature alloy heterojunction and its welding method.

[0021] like Figure 1 As shown, an embodiment of the present invention provides a welding method for a ceramic matrix composite / high-temperature alloy heterojunction, comprising the following steps: S1: A carbon or boron cladding is pre-formed on the welding surface of the ceramic matrix composite material. This cladding is then transformed into a carbon or boron sacrificial layer through vacuum heat treatment or annealing. The carbon cladding can be pre-formed in various ways, such as coating the surface of the ceramic matrix composite material with a carbon source solution (e.g., sugar solution, asphalt solution), followed by drying and carbonization; or depositing a carbon layer on the surface of the ceramic matrix composite material using methods such as chemical vapor deposition (CVD) or physical vapor deposition (PVD). A boron cladding can also be pre-formed in a similar manner, such as coating the surface with a boron source solution (e.g., boric acid solution), followed by drying and heat treatment; or forming a boron layer on the surface of the ceramic matrix composite material using methods such as sputtering deposition or evaporation deposition. After pre-formation, the carbon or boron cladding needs to undergo heat treatment to transform into a sacrificial layer. For example, the carbon cladding can be subjected to high-temperature treatment in an inert or reducing atmosphere to change its structure and form a carbon sacrificial layer with specific reactivity. Boron coatings can be heat-treated at lower temperatures, such as by annealing in a vacuum or inert atmosphere, to transform them into boron sacrificial layers.

[0022] S2: An active solder with a face-centered cubic (FCC) matrix and added active elements Ti, V, or Cr. The matrix material of the active solder can be a metal with a FCC crystal structure, such as pure copper, pure nickel, pure cobalt, or their alloys, to ensure good weld plasticity. The active elements Ti, V, or Cr are added to the solder to react with the sacrificial layer during the welding process. The active solder can be prepared using conventional melting methods, such as induction melting under a protective atmosphere, to obtain a uniform alloy composition.

[0023] S3: A sandwich structure is assembled from ceramic matrix composites, active brazing filler metal, and high-temperature alloys, and vacuum welded. During assembly, the active brazing filler metal is placed between the pre-formed sacrificial layer of the ceramic matrix composite and the high-temperature alloy, forming a layered structure of "ceramic matrix composite / sacrificial layer / active brazing filler metal / high-temperature alloy". The carbon or boron sacrificial layer directionally attracts and reacts with active elements (such as Ti, V, or Cr), transforming the carbon or boron sacrificial layer into a carbon or boron barrier layer in situ. These in-situ formed barrier layers effectively inhibit the direct reaction between active elements and the ceramic matrix composite matrix (such as SiC), thereby avoiding the formation of brittle silicides or intermetallic compounds. This results in a weld seam retaining only a face-centered cubic structure, constructing a fully plastic weld interface, and obtaining a ceramic matrix composite / high-temperature alloy heterojunction.

[0024] Specifically, ceramic matrix composites (CMC) generally refer to composite materials with ceramic fibers reinforcing a ceramic matrix, such as SiCf / SiC composites. They have excellent properties such as low density and high temperature resistance and are often used in hot-end components such as aero-engines.

[0025] High-temperature alloys generally refer to metal alloys that have excellent strength, oxidation resistance and corrosion resistance in high-temperature environments. For example, Co-based GH5188 alloy is often used as structural components for aero-engines.

[0026] Heterogeneous joints refer to joints formed by two or more different materials through a connection process. In this application, it specifically refers to the connection structure formed by ceramic matrix composite materials and high-temperature alloys.

[0027] Carbon cladding or boron cladding refers to a thin layer, mainly composed of carbon or boron, pre-prepared on the welding surface of ceramic matrix composites, which serves as a precursor for the subsequent formation of a sacrificial layer.

[0028] A carbon sacrificial layer or a boron sacrificial layer refers to a thin layer of carbon or boron formed by specific treatment of a carbon or boron cladding, which can preferentially react with the active elements in the active solder during the welding process.

[0029] Active brazing filler metal refers to brazing materials containing active elements (such as Ti, V, Cr) that can react with ceramic matrix composites or sacrificial layers. Its matrix is ​​usually face-centered cubic to provide good plasticity.

[0030] Face-centered cubic (FCC) refers to a type of crystal structure that has good plasticity and toughness, which helps to alleviate residual stress in welded joints.

[0031] Active elements refer to elements that can chemically react with ceramic matrix composites or sacrificial layers during brazing, such as titanium (Ti), vanadium (V), or chromium (Cr).

[0032] A carbon barrier layer or a boron barrier layer refers to a thin layer of carbide or boron compound formed during the welding process by the in-situ reaction of a carbon sacrificial layer or a boron sacrificial layer with an active element, which can effectively inhibit the direct reaction between the active element and the ceramic matrix composite material.

[0033] A fully plastic weld interface refers to a weld area that is mainly composed of a face-centered cubic structure with good plasticity, which can effectively relieve thermal stress and avoid the formation of brittle phases through plastic deformation.

[0034] In this embodiment, a sacrificial layer is prefabricated on the surface of the ceramic matrix composite material (CMC). During welding, this sacrificial layer directionally attracts active elements (Ti, V, or Cr) from the FCC-based active solder and reacts with these elements in situ. Utilizing the strong reactivity between the sacrificial layer and the FCC-based active elements, the sacrificial layer undergoes an in-situ transformation into a barrier layer. This barrier layer adheres tightly and densely to the CMC surface, inhibiting excessive CMC decomposition and the formation of harmful silicides at the source. It prevents silicides from entering the weld and forming brittle silicides or intermetallic compounds, effectively suppressing the decomposition of the CMC and the formation of brittle phases. This results in only a complete face-centered cubic plastic structure remaining in the weld, thus constructing a fully plastic weld interface in the heterogeneous connection of the CMC and the high-temperature alloy. This successfully resolves the contradiction of balancing "reaction control" and "stress relief" in traditional connections, achieving a high-strength, high-thermal-stability, and high-sealing CMC / high-temperature alloy heterogeneous joint.

[0035] Optionally, S1 includes: dissolving phenolic resin in acetone to prepare a phenolic resin organic solution, placing the ceramic matrix composite material in the phenolic resin organic solution for vacuum impregnation, and curing it in an air atmosphere to achieve a pre-coated carbon layer on the welding surface of the ceramic matrix composite material.

[0036] Specifically, a phenolic resin (PF) organic solution is prepared by dissolving phenolic resin (PF) in acetone. The aim is to create a homogeneous and stable organic solution, ensuring that the phenolic resin is uniformly distributed on the surface of the ceramic matrix composite during subsequent coating or impregnation, thus laying the foundation for the formation of a continuous and dense carbon coating. Phenolic resin, as a thermosetting resin, forms carbon after high-temperature carbonization, exhibiting good heat resistance and mechanical strength. Acetone, as a commonly used organic solvent, has good solubility and volatility. Besides acetone, other organic solvents or mixed solvents such as ethanol and methanol can be used to dissolve the phenolic resin. Physical methods such as stirring and ultrasonic dispersion can be used to assist dissolution, accelerating the dissolution process and ensuring the homogeneity of the solution.

[0037] Vacuum impregnation of ceramic matrix composites in a phenolic resin organic solution aims to utilize the suction effect of vacuum to fully penetrate the micropores on the surface of the ceramic matrix composite, ensuring a good mechanical interlock and chemical bond between the coating and the substrate. This improves the adhesion and continuity of the coating, preventing voids or uneven areas. Parameters such as the vacuum level and impregnation time during the impregnation process can be optimized based on the porosity of the ceramic matrix composite and the viscosity of the solution. For example, segmented vacuum impregnation can be used, either by first applying vacuum and then impregnating, or by continuously applying vacuum during the impregnation process. Besides vacuum impregnation, other methods such as brushing, spraying, and roller coating can also be used to apply the solution to the surface of the ceramic matrix composite, but vacuum impregnation has significant advantages in terms of penetration and uniformity.

[0038] Curing in an air atmosphere aims to induce a cross-linking reaction in the impregnated phenolic resin, forming a stable solid coating. Oxygen in the air atmosphere may participate in or promote certain curing reactions. Simultaneously, the curing process facilitates solvent evaporation, resulting in a denser and more stable coating structure, enhancing the adhesion between the coating and the ceramic matrix composite, and providing a solid foundation for subsequent heat treatment to form a carbon sacrificial layer. Curing temperature and time are key parameters and can be adjusted according to the type of phenolic resin and the desired degree of curing. For example, curing can be performed at room temperature for an extended period or by baking at a specific temperature. Besides air, curing can also be carried out in an inert atmosphere (such as nitrogen) to avoid oxidation; however, air curing is simpler, less expensive, and feasible for curing phenolic resins.

[0039] In this optional embodiment, phenolic resin is used as a carbon source precursor, and combined with vacuum impregnation and air curing processes, a continuous, dense carbon coating with good adhesion to the substrate can be formed on the welding surface of the ceramic matrix composite. This high-quality carbon coating serves as a precursor for the subsequent carbon sacrificial layer, effectively avoiding problems such as voids, unevenness, or poor adhesion during the prefabrication process. This provides a solid foundation for the transformation of the carbon coating into a carbon sacrificial layer through vacuum heat treatment in the subsequent S1 step, thereby ensuring that the carbon sacrificial layer can uniformly and effectively attract and react with active elements, ultimately achieving in-situ formation of the carbon barrier layer. This constructs a fully plastic weld interface, effectively inhibiting the decomposition of the ceramic matrix composite and the formation of harmful silicides / intermetallic compounds, significantly improving the performance of the ceramic matrix composite / high-temperature alloy heterojunction.

[0040] Specifically, the phenolic resin in the organic solution has a phenolic resin mass fraction of 15 wt.% to 35 wt.%. The cleaned CMC is then placed in a PF solution for vacuum impregnation: the vacuum degree is approximately 0.9 × 10⁻⁶. -1The pressure is set at MPa, and the impregnation time is approximately 15 min to promote resin penetration into surface micropores / defects. After impregnation, the resin is cured at 110 °C in air for approximately 1 h to form a carbon coating.

[0041] Optionally, S1 includes: dissolving dopamine powder in alcohol to prepare a dopamine organic solution, spin-coating the dopamine organic solution onto the welding surface of the ceramic matrix composite material, and vacuum drying and curing to achieve a pre-coated carbon layer on the welding surface of the ceramic matrix composite material.

[0042] Specifically, in preparing the dopamine organic solution, dopamine powder, as a carbon source precursor, possesses self-polymerization properties and can form a polydopamine film on the surface of various substrates. This film can be converted into a carbon layer after heat treatment. Alcohol, such as ethanol, isopropanol, or methanol, can effectively dissolve the dopamine powder, forming a homogeneous and stable dopamine organic solution. Its moderate volatility and good wettability on the surface of ceramic matrix composites contribute to uniform solution spreading. Besides alcohol, other polar organic solvents, such as acetone or tetrahydrofuran, can also be used, as long as they can effectively dissolve dopamine and ensure solution stability. This step aims to obtain a homogeneous precursor solution for subsequent coating, ensuring the uniformity of composition and thickness of the final carbon coating.

[0043] Subsequently, the dopamine organic solution is spin-coated onto the welding surface of the ceramic matrix composite material. Spin coating is a highly efficient and precise thin film preparation technique. By rotating the substrate at high speed and using centrifugal force to remove excess solution, a thin film of uniform, continuous, and controllable thickness is formed on the substrate surface. For this application, spin coating ensures that the dopamine organic solution forms a dense, defect-free pre-coated carbon layer on the welding surface of the ceramic matrix composite material, which is crucial for the subsequent formation of the carbon sacrificial layer and its barrier effect. In addition to spin coating, dip coating, spray coating, or blade coating can also be used, but spin coating has significant advantages in controlling the uniformity and thickness of the film.

[0044] Finally, vacuum drying and curing are performed. This step aims to remove the solvent from the dopamine organic solution and promote the polymerization reaction of dopamine on the surface of the ceramic matrix composite to form a stable polydopamine film. Drying in a vacuum environment effectively lowers the boiling point of the solvent, accelerates solvent evaporation, and avoids the formation of bubbles or defects due to rapid solvent evaporation during the drying process, thus ensuring the density of the coating. At the same time, the vacuum environment also helps to inhibit oxidation, ensuring the pure conversion of polydopamine. The curing process further enhances the bonding force between the polydopamine film and the ceramic matrix composite, making it less prone to detachment and laying a solid foundation for subsequent heat treatment to transform it into a carbon sacrificial layer. The curing temperature and time can be optimized according to the polymerization characteristics of dopamine and the desired coating strength.

[0045] In this optional embodiment, dopamine is used as a carbon source precursor. Leveraging its self-polymerization properties on various substrate surfaces and combined with spin-coating technology, a continuous, dense, and firmly bonded carbon coating is pre-formed on the welding surface of the ceramic matrix composite material. This pre-formed carbon coating effectively solves the problem of weak or discontinuous bonding between the coating and the ceramic matrix composite material, providing a solid foundation for its subsequent in-situ transformation into a carbon sacrificial layer through vacuum heat treatment. When this carbon sacrificial layer directionally attracts and reacts with active elements during welding, it can more effectively transform into a continuous and dense carbon barrier layer in situ. This inhibits excessive decomposition of the ceramic matrix composite material and the formation of harmful silicides from the source, ultimately contributing to the construction of a fully plastic weld interface and improving the overall performance and reliability of the ceramic matrix composite / high-temperature alloy heterojunction.

[0046] Specifically, the dopamine solution contained 15 wt.% to 35 wt.% dopamine by mass. The mixed dopamine solution was spin-coated onto CMC samples (approximately 2000 rpm × 40 s) and then incubated in a vacuum chamber (vacuum degree approximately 0.9 × 10⁻⁶). -1 The material is placed in an environment with a pressure of MPa and a temperature of 40~60°C for 4 to 14 hours to dry and cure, forming a carbon coating.

[0047] Optionally, S1 includes: performing vacuum heat treatment on the carbon coating at 800°C to 1100°C for more than 10 minutes in a vacuum environment, so that the carbon coating is transformed into a carbon sacrificial layer.

[0048] Specifically, the vacuum environment is designed to provide an oxygen-free and pollution-free atmosphere to prevent oxidation or decomposition of the carbon coating during high-temperature heat treatment, thereby effectively maintaining its structural integrity and chemical purity. For example, the pressure inside the heat treatment furnace can be reduced to 10 by using a high-vacuum pump. -3 Pa to 10 -5The process involves heat treatment under ultra-high vacuum conditions (e.g., Pa) or in the presence of an inert gas (such as high-purity argon or nitrogen) to ensure the removal of oxygen and reactive impurities. Specifically, the carbon coating is held at temperatures between 800°C and 1100°C for at least 10 minutes to provide sufficient heat input and reaction time. This promotes thorough reaction and structural reorganization within the carbon coating, for example, inducing the transformation of amorphous carbon into graphitized carbon or optimizing its crystal structure, thereby ensuring the complete transformation of the carbon coating into a carbon sacrificial layer with the desired chemical activity. In practice, the ceramic matrix composite can be heated to 900°C at a heating rate of 5°C / min to 10°C / min and held at this temperature for 15 minutes; or heated to 1000°C and held for 20 minutes. Through this vacuum heat treatment process, the carbon coating is effectively transformed into a carbon sacrificial layer. This means that the carbon coating has undergone changes in its microstructure and chemical properties, enabling it to more effectively play its "sacrificial" role in the subsequent welding process. That is, it can directionally attract and react with the active elements in the active brazing filler metal, thereby forming a continuous and dense carbon barrier layer in situ, laying a solid foundation for building a fully plastic weld interface.

[0049] In this optional embodiment, firstly, the introduction of a vacuum environment effectively eliminates oxygen and reactive gases, preventing the carbon coating from oxidizing or decomposing at high temperatures, thus ensuring the structural integrity and chemical purity of the carbon coating and providing a stable precursor for subsequent conversion. Secondly, precisely limiting the heat treatment temperature to the range of 800°C to 1100°C and ensuring a holding time of more than 10 minutes provides sufficient thermal energy and reaction kinetics, allowing the carbon coating to undergo sufficient structural reorganization and phase transformation, such as the transformation from amorphous carbon to more stable graphitized carbon, thereby ensuring that the carbon coating can be completely and uniformly transformed into a carbon sacrificial layer with the expected chemical activity. This sufficient and stable transformation allows the formed carbon sacrificial layer to more effectively attract active elements in the active solder during subsequent vacuum welding and react with them in situ, ultimately forming a continuous, dense carbon barrier layer that is well bonded to the ceramic matrix composite material. This fundamentally inhibits the excessive decomposition of ceramic matrix composites and the formation of harmful silicides or intermetallic compounds, thereby ensuring that the weld retains only the face-centered cubic structure, successfully constructing a fully plastic weld interface, significantly improving the strength, toughness and high-temperature stability of ceramic matrix composite / high-temperature alloy heterojunctions, and effectively solving the contradiction of "reaction control-stress relief" being difficult to balance.

[0050] Optionally, S1 includes: performing radio frequency magnetron sputtering on the welding surface of the ceramic matrix composite material using a boron target under an inert gas atmosphere to sputter and deposit a boron coating on the welding surface of the ceramic matrix composite material, the thickness of the boron coating being 100 nm to 1 μm.

[0051] Specifically, the operation is carried out in an inert gas atmosphere to eliminate reactive gases such as oxygen and water vapor, preventing boron from reacting with these gases during deposition to form oxide impurities, thus ensuring the purity of the boron coating. Commonly used inert gases include high-purity argon, with a purity of over 99.999%. A boron target is used as the sputtering source, its main component being high-purity boron, directly providing boron atoms or ions to ensure the deposited coating is pure boron and avoid the introduction of impurities. The purity of the boron target is typically required to be above 99.5%. Radio frequency magnetron sputtering is performed on the weld surface of the ceramic matrix composite material. Utilizing the sputtering characteristics of radio frequency power supplies suitable for non-conductive or low-conductive materials, and setting a magnetic field on the back of the target, the plasma is confined near the target surface, thereby improving sputtering efficiency and film quality. Radio frequency magnetron sputtering can effectively activate the surface of the ceramic matrix composite material, promoting the bonding of boron atoms to the substrate surface and improving the adhesion of the coating. By sputtering the deposited boron coating, a continuous and dense boron film is formed, serving as the basis for subsequent transformation into a boron sacrificial layer. The deposition rate and uniformity can be controlled by adjusting parameters such as RF power, operating gas pressure, and target-substrate distance. The thickness of the boron coating is limited to 100 nm to 1 μm to ensure that the coating is neither too thick, leading to excessive internal stress and easy cracking, nor too thin, resulting in insufficient barrier effect. For example, if the thickness is less than 100 nm, a continuous and effective barrier layer may not be formed; if the thickness is greater than 1 μm, it may increase internal stress, affecting the bonding stability between the coating and the substrate, and even causing peeling during subsequent heat treatment. This thickness range aims to balance barrier effect and interface stability.

[0052] In this optional embodiment, the use of radio frequency magnetron sputtering technology in an inert gas atmosphere and precise control of the boron coating thickness effectively avoids problems such as poor adhesion between the coating and the substrate, insufficient coating continuity, or uneven thickness caused by improper atmosphere control or mismatched process parameters in traditional sputtering methods. The inert gas atmosphere ensures the purity of the boron coating and avoids the generation of harmful oxides; radio frequency magnetron sputtering technology significantly improves the adhesion and density of the boron coating to the welded surface of the ceramic matrix composite by enhancing plasma uniformity and promoting atomic-level bonding. At the same time, precisely controlling the thickness of the boron coating within the range of 100 nm to 1 μm ensures that the coating has sufficient barrier capacity while avoiding the risk of internal stress concentration and cracking caused by excessive thickness. This high-quality, high-stability boron coating lays a solid foundation for the stable transformation of the boron coating into a boron sacrificial layer in the subsequent S1 step. It further ensures that the boron sacrificial layer can effectively attract active elements in the direction of the S3 step and transform into a continuous and dense boron barrier layer in situ. This suppresses the excessive decomposition of ceramic matrix composites and the formation of harmful silicides from the source, and ultimately helps to build a fully plastic weld interface and realize the preparation of high-performance ceramic matrix composite / high-temperature alloy heterojunctions.

[0053] Specifically, a boron target (B or B4C) is mounted on the magnetron sputtering system, and the vacuum is evacuated to 1×10⁻⁶. -3 Up to 1×10 4 The CMC was cleaned / activated with Ar plasma (50 W to 200 W, 1 min to 5 min) to remove surface contaminants and improve film adhesion. Ar was introduced as the working gas, and the working pressure was stabilized at a preferred range of 0.3 Pa to 1.0 Pa. Due to the low conductivity of boron, radio frequency (RF) magnetron sputtering was preferably used for deposition. A thin layer of boron was sputtered at an RF power of 100 W to 300 W and a substrate temperature preferably between room temperature and 200 °C, and sample rotation was activated to ensure uniform coverage.

[0054] Optionally, S1 includes: annealing the boron coating at 150°C to 300°C for 0.5 h to 2 h in a vacuum or inert atmosphere to transform the boron coating into a boron sacrificial layer.

[0055] Specifically, annealing in a vacuum or inert atmosphere aims to provide an oxygen-free environment to prevent oxidation of the boron coating at high temperatures, thereby ensuring the purity of the boron coating and its effective conversion into a boron sacrificial layer. For example, in addition to a vacuum environment, the inert atmosphere can be high-purity argon, high-purity nitrogen, or a mixture thereof. These gases can effectively isolate oxygen, preventing boron from reacting with oxygen to form boron oxide, which would affect the subsequent function of the sacrificial layer.

[0056] Annealing the boron coating at a temperature range of 150°C to 300°C is intended to precisely control the phase transformation and structural rearrangement of the boron coating, enabling it to be fully activated and transformed into a boron sacrificial layer with specific chemical activity. If the annealing temperature is too low, the boron coating may not be fully activated, resulting in incomplete transformation; if the annealing temperature is too high, it may trigger unnecessary side reactions or lead to excessive boron volatilization, thereby affecting the uniformity and stability of the boron sacrificial layer.

[0057] The annealing time is set between 0.5 h and 2 h to ensure sufficient time for the boron coating to complete its transformation into a boron sacrificial layer, while avoiding increased energy consumption or material performance degradation due to excessive time. Within this time range, boron atoms can fully diffuse and rearrange to form a stable boron sacrificial layer structure. For example, at 150°C, an annealing time of nearly 2 hours may be required to ensure full transformation, while at 300°C, 0.5 hours may be sufficient to achieve the desired effect.

[0058] Through the precisely controlled annealing process described above, the boron cladding is effectively transformed into the boron sacrificial layer. This boron sacrificial layer possesses specific chemical activity, enabling it to directionally attract and react with active elements Ti, V, or Cr in the active solder during the subsequent vacuum welding S3 process, thereby achieving in-situ transformation of the boron sacrificial layer into a boron barrier layer. This transformation is a crucial prerequisite for constructing a fully plastic weld interface and suppressing the formation of brittle phases.

[0059] In this optional embodiment, the transformation process of the boron cladding to a boron sacrificial layer is precisely controlled by annealing the boron cladding at 150°C to 300°C for 0.5 h to 2 h in a vacuum or inert atmosphere. Annealing in a vacuum or inert atmosphere effectively avoids the oxidation of boron at high temperatures, ensuring the purity and activity of the boron sacrificial layer. The specific temperature range (150°C to 300°C) and time range (0.5 h to 2 h) ensure that the boron cladding is fully and uniformly activated, forming a boron sacrificial layer with stable chemical activity. This precisely controlled transformation process lays a solid foundation for the subsequent directional attraction of active elements by the boron sacrificial layer to transform into a boron barrier layer in situ during welding S3, thereby effectively inhibiting the formation of brittle silicides or intermetallic compounds, ensuring that the weld retains only a face-centered cubic structure, and ultimately constructing a fully plastic weld interface, significantly improving the mechanical properties and high-temperature stability of the ceramic matrix composite / high-temperature alloy heterojunction.

[0060] Optionally, in S2, the proportion of active elements in the active solder does not exceed 20 at.%, and the active solder components are prepared by vacuum arc melting with a melting vacuum of 1×10⁻⁶. -3 Pa to 1×10 -2 Pa, melting current is 450 A to 500 A.

[0061] Specifically, "the proportion of active elements not exceeding 20 at.%" means that the atomic percentage content of active elements such as Ti, V, or Cr in the active solder is precisely controlled below 20%. This limitation aims to ensure that the active elements can react appropriately with the carbon or boron sacrificial layer during soldering to form a continuous and dense carbon or boron barrier layer, while avoiding excessive reaction caused by an excess of active elements. For example, when preparing the active solder, the mass of each component raw material can be accurately weighed, and the corresponding atomic percentage can be calculated based on its atomic weight, thereby controlling the content of active elements within a preset range before melting. In addition, after the solder is melted, the actual composition of the solder can be detected using analytical methods such as inductively coupled plasma optical emission spectroscopy (ICP-OES) or energy-dispersive X-ray spectroscopy (EDS) to verify whether the content of active elements meets the requirements. If there is a deviation, adjustments or re-formulation are made.

[0062] "Preparation of active solder components using vacuum arc melting" refers to melting and mixing the constituent elements of the active solder in a vacuum environment using the high temperatures generated by an electric arc discharge to form a homogeneous alloy. This preparation method effectively avoids reactions between the solder and oxygen, nitrogen, and other gases in the air during the high-temperature melting process, thereby reducing the formation of impurities such as oxides and nitrides and ensuring the purity of the solder. Specifically, pre-proportioned metal raw materials are placed in a water-cooled copper crucible. After being evacuated to a high vacuum in a vacuum arc melting furnace, an electric arc is generated between a tungsten electrode and the raw materials, causing the raw materials to melt rapidly and mix thoroughly. To further improve the uniformity of the solder, multiple turning melting processes are usually performed.

[0063] "The smelting vacuum is 1×10" -3 Pa to 1×10 -2 "Pa" refers to the pressure within the furnace chamber being strictly controlled at 1×10⁻⁶ during the vacuum arc melting process. -3 Pa to 1×10 -2 Within the range of Pa. This high vacuum level minimizes the contact between residual gas molecules and the molten solder, thereby suppressing solder oxidation and contamination, ensuring the metallurgical quality of the solder and the stability of subsequent welding performance. Achieving this vacuum level typically requires a high-performance vacuum pump assembly, such as a composite vacuum system consisting of mechanical pumps, diffusion pumps, or molecular pumps, and real-time monitoring and feedback control via a high-precision vacuum gauge.

[0064] "Melting current of 450 A to 500 A" refers to the current intensity through the electrodes being precisely set between 450 amperes and 500 amperes during the vacuum arc melting process. This current range is optimized to provide sufficient energy for the solder components to fully melt and mix uniformly, while avoiding excessive evaporation due to excessive current or incomplete melting due to insufficient current. By adjusting the power output of the arc melting equipment, the current can be precisely controlled to adapt to the melting characteristics of different solder systems, thereby ensuring the stability and consistency of the solder components' performance.

[0065] In this optional embodiment, the content of active elements in the active brazing filler metal can be precisely controlled to avoid excessive reaction between the active elements and the ceramic matrix composite material, thereby inhibiting the formation of brittle silicides or intermetallic compounds. Simultaneously, the brazing filler metal is prepared using vacuum arc melting under specific high vacuum and current conditions, ensuring high purity and compositional uniformity and preventing impurities from interfering with the reaction process. This allows the carbon or boron sacrificial layer to directionally attract and controllably react with the active elements in the subsequent vacuum welding step S3, transforming in situ into a continuous and dense carbon or boron barrier layer, effectively preventing excessive decomposition of the ceramic matrix composite material and the formation of harmful phases. Ultimately, the weld seam retains only a face-centered cubic structure, successfully constructing a fully plastic weld interface, significantly improving the strength and toughness of the ceramic matrix composite / high-temperature alloy dissimilar joint, effectively alleviating residual thermal stress caused by thermal expansion coefficient mismatch, and thus achieving a highly reliable connection.

[0066] Optionally, S3 includes: mixing active solder with a particle size D50 of 5 μm to 30 μm with terpineol to form a solder slurry; degassing the solder slurry under vacuum; coating it onto the welding surface of the ceramic matrix composite material by scraping or screen printing; drying it under vacuum conditions of 50°C to 80°C and -0.08 MPa to -0.095 MPa for 2 h to 8 h to remove terpineol; and drying to form a solder interlayer of 50 μm to 300 μm.

[0067] Specifically, the particle size D50 of the active solder is controlled within the range of 5 μm to 30 μm to ensure a suitable size distribution of the solder particles. This particle size range effectively avoids uneven coating or clogging of the coating equipment due to excessively large particles, while also preventing excessively small particles from agglomerating and affecting the flowability of the slurry and the coating quality. For example, methods such as fine grinding, sieving, or air classifying can be used to control the particle size of the active solder to obtain the required particle size distribution.

[0068] The purpose of mixing active solder with terpineol is to prepare a solder slurry with good rheological properties. Terpineol, as an organic solvent and binder, provides a uniform dispersion medium for the solder particles and imparts appropriate viscosity and thixotropy to the slurry, making it easy to spread and level during coating and stable during standing, preventing solder particle sedimentation. Besides terpineol, other organic solvents with similar properties can also be used, such as mixtures of ethyl cellulose and terpene alcohols, or combinations of acrylate binders with organic solvents.

[0069] Vacuum degassing of brazing filler metal slurry aims to remove any tiny air bubbles that may be present in the slurry. If these bubbles are not removed, they can form pores or defects during subsequent welding, reducing the density and mechanical properties of the weld. Vacuum degassing is typically achieved by placing the slurry in a vacuum environment, using the pressure difference to cause the bubbles to expand and escape from the slurry surface. Alternatively, mechanical stirring or ultrasonic vibration can be used as auxiliary methods to improve degassing efficiency.

[0070] Solder paste is applied to the welding surface of ceramic matrix composites using either scraping or screen printing methods, aiming to achieve uniform, continuous coverage and precise thickness control of the solder layer. Scraping is suitable for large-area, uniform coating, where a scraper spreads the paste evenly. Screen printing is suitable for precise coating of complex patterns or specific areas, where a screen presses the paste onto the substrate surface. Both methods effectively avoid the unevenness that can occur with manual coating, ensuring good contact between the solder layer and the substrate.

[0071] Drying at specific temperatures (50 °C to 80 °C) and vacuum levels (-0.08 MPa to -0.095 MPa) for 2 to 8 hours aims to completely remove terpineol solvent from the solder slurry. Moderate heating helps accelerate the volatilization of terpineol, while the vacuum environment lowers its boiling point, further promoting complete evaporation and preventing solvent residue. Complete solvent removal is crucial to prevent porosity, weld contamination, or impaired wettability of the solder during subsequent soldering. The drying time must be optimized based on the solder layer thickness, solvent type, and environmental conditions to ensure complete drying.

[0072] Through the aforementioned drying process, a brazing filler metal layer with a thickness ranging from 50 μm to 300 μm is formed on the welding surface of the ceramic matrix composite. This thickness range of the brazing filler metal layer is carefully designed to provide sufficient brazing filler metal for subsequent vacuum welding, while avoiding problems caused by excessive thickness or thinness. The appropriate thickness ensures that the brazing filler metal fully fills the weld gap after melting, promoting the reaction between the active elements and the sacrificial layer, while also effectively controlling the final weld thickness, reducing overflow due to excessive brazing filler metal or incomplete welding due to insufficient brazing filler metal.

[0073] In this optional embodiment, problems such as poor uniformity, air bubbles, and inconsistent interlayer thickness that may occur in brazing filler metal applications are effectively solved, thereby significantly improving welding quality and the formation effect of the subsequent barrier layer. Specifically, by precisely controlling the particle size D50 of the active brazing filler metal between 5 μm and 30 μm, the appropriate size of the brazing filler metal particles is ensured, avoiding uneven coating and agglomeration, laying the foundation for the preparation of high-quality brazing filler metal slurry. The active brazing filler metal is mixed with terpineol to form a brazing filler metal slurry. The excellent dispersing and binding properties of terpineol allow the brazing filler metal particles to be uniformly dispersed and impart good rheological properties to the slurry, facilitating subsequent coating operations. Vacuum degassing of the brazing filler metal slurry completely removes air bubbles, effectively avoiding porosity defects caused by residual air bubbles during welding and ensuring the density of the weld. Precision coating techniques such as scraping or screen printing are used to achieve uniform and continuous coverage of the brazing filler metal slurry on the welding surface of the ceramic matrix composite material, and the thickness of the brazing filler metal layer can be precisely controlled, ensuring good contact between the brazing filler metal and the substrate. Drying at 50 °C to 80 °C and a vacuum environment of -0.08 MPa to -0.095 MPa for 2 h to 8 h efficiently and thoroughly removes terpineol solvent, avoiding the negative impact of solvent residue on welding quality, such as porosity or weld contamination. The resulting 50 μm to 300 μm brazing filler metal layer, with its optimized thickness, provides sufficient brazing filler metal to promote the full reaction between active elements and the carbon or boron sacrificial layer, achieving in-situ transformation of the carbon or boron barrier layer, while effectively controlling the final weld thickness, providing a solid foundation for constructing a fully plastic weld interface. Overall, these refined brazing filler metal preparation and coating processes ensure the uniformity, density, and precision of the brazing filler metal layer, thereby creating ideal conditions for the directional reaction between active elements and the sacrificial layer in subsequent vacuum welding. Ultimately, this helps to form a high-quality carbon or boron barrier layer and construct a weld interface with excellent plastic deformation capabilities, effectively alleviating residual thermal stress caused by thermal expansion coefficient mismatch and improving the overall performance of ceramic matrix composite / high-temperature alloy heterojunctions.

[0074] Optionally, the mass ratio of active solder powder to terpineol is 80:20 to 92:8, and the solder slurry is vacuum degassed after stirring / ball milling for 1 to 4 hours. It is then coated onto the areas to be joined by scraping or screen printing, forming a 50 μm to 150 μm solder layer after a single coating and drying. If necessary, it can be coated 2 to 3 times to obtain a 50 μm to 300 μm solder interlayer. Optionally, S3 includes: heating to the welding temperature range at a heating rate of 3 ℃ / min to 8 ℃ / min and holding at that temperature for 10 min to 30 min to perform vacuum welding, wherein the welding temperature range is the melting point temperature of the active brazing filler metal plus 50 ℃ to 200 ℃.

[0075] Specifically, during vacuum welding, the heating rate is precisely controlled, set within the range of 3 °C / min to 8 °C / min. This control of the heating rate is crucial to avoid excessive thermal stress on the material during rapid heating, while also ensuring welding efficiency. For example, precise adjustment can be achieved through the heating power and temperature feedback system of the vacuum furnace, using a PID controller to control the output power of the heating elements in real time, ensuring that the furnace temperature rises steadily according to a preset curve. Alternatively, a multi-zone heating furnace can be used, independently controlling the power of different heating zones to achieve uniform heating of the entire welding area, and adjusting the heating rate of each zone according to the thermal response characteristics of the material.

[0076] Furthermore, this application sets the welding temperature range to the melting point temperature of the active solder plus 50 °C to 200 °C. This temperature range is chosen to ensure that the active solder can fully melt, wet, and react with the substrate, while avoiding excessive temperature that could lead to excessive decomposition of the ceramic matrix composite or the formation of harmful brittle phases. In practice, the melting point temperature of the selected active solder can be accurately determined using differential scanning calorimetry (DSC) or a thermal analyzer. A suitable welding temperature range can then be calculated based on this melting point temperature and set as the target temperature for the vacuum furnace. Alternatively, by combining the phase diagram of the solder and the heat resistance properties of the material, the optimal welding temperature range can be determined through small-batch trials to ensure good fluidity and wettability of the solder, while limiting the degree of interfacial reaction and avoiding the formation of excessive brittle intermetallic compounds.

[0077] After reaching the welding temperature range, a holding period of 10 to 30 minutes is performed. This holding time is set to ensure sufficient time for the active elements and the sacrificial layer to react fully, promoting the complete transformation of the carbon or boron sacrificial layer into a carbon or boron barrier layer, and allowing the brazing filler metal to fully fill the weld, forming a dense bond. During vacuum welding, once the set welding temperature range is reached, the duration of the holding phase is precisely controlled by a timer to ensure that the interface reaction and full diffusion of the brazing filler metal are completed within the preset 10 to 30 minutes. Alternatively, a real-time monitoring system can be used, such as in-situ high-temperature X-ray diffraction (HT-XRD) or acoustic emission technology, to monitor the progress of the interface reaction. When it is detected that the carbon or boron sacrificial layer has been completely transformed into a barrier layer and the brazing filler metal has been fully wetted and filled, the holding phase can be ended, thereby optimizing the holding time.

[0078] In this optional embodiment, precise control of the heating rate, welding temperature range, and holding time constructs an optimized welding thermal cycle process. This precise thermal cycle control effectively avoids thermal stress concentration caused by excessively rapid heating or prolonged process time due to excessively slow heating. Simultaneously, it ensures that the active brazing filler metal fully melts and flows at a suitable temperature, promoting interfacial bonding. More importantly, within the set holding time, the active elements can fully react with the pre-formed carbon or boron sacrificial layer, achieving in-situ and uniform transformation into a continuous and dense carbon or boron barrier layer. This barrier layer effectively inhibits excessive decomposition of the ceramic matrix composite material and the diffusion of silicon into the weld, thereby preventing the formation of brittle silicides or intermetallic compounds from the source. Ultimately, the weld retains only a face-centered cubic structure, constructing a fully plastic weld interface, significantly improving the plasticity, joint strength, and overall reliability of the ceramic matrix composite / high-temperature alloy heterogeneous joint, effectively resolving the contradiction of balancing "reaction control—stress relief" in heterogeneous joining.

[0079] Optionally, the vacuum degree during vacuum welding is approximately 10. -6 Torr, after vacuum welding, is cooled to room temperature at approximately 5°C / min to 10°C / min.

[0080] Another embodiment of the present invention provides a ceramic matrix composite / high-temperature alloy heterojunction, which is manufactured using the welding method for ceramic matrix composite / high-temperature alloy heterojunctions as described above.

[0081] Specifically, the joint forms a continuous, dense barrier layer (carbon or boron barrier layer) that bonds well with the ceramic matrix composite material between the ceramic matrix composite and the weld. This barrier layer is formed in situ during the welding process through a directional reaction between a pre-formed carbon or boron cladding and active elements in the active solder. This in-situ formed barrier layer effectively inhibits the decomposition of the ceramic matrix composite material during high-temperature welding and prevents silicon from diffusing into the weld area, thereby fundamentally avoiding the formation of brittle silicides or intermetallic compounds.

[0082] The weld region of this joint is primarily composed of a face-centered cubic structure, exhibiting excellent plasticity. This is because the welding method utilizes a sacrificial layer to directionally attract and react with active elements, ensuring that only the face-centered cubic matrix structure of the active solder remains in the weld, thus avoiding the brittle phases that would result from the reaction of active elements with the ceramic matrix composite. This fully plastic weld interface is crucial for achieving stress relief and high reliability in the joint.

[0083] In this embodiment, the interface structure and performance of the prepared ceramic matrix composite / high-temperature alloy heterojunction are significantly optimized. Due to the specific welding method employed, during the welding process, the pre-formed sacrificial layer on the surface of the ceramic matrix composite directionally attracts active elements from the active brazing filler metal and transforms them in situ into a continuous, dense barrier layer. This barrier layer effectively isolates the ceramic matrix composite from the active brazing filler metal, inhibiting excessive decomposition of the ceramic matrix composite and the diffusion of silicon into the weld from the source, thereby preventing the formation of brittle silicides and intermetallic compounds. Simultaneously, because the active elements are effectively consumed by the barrier layer, the weld region maintains a pure face-centered cubic structure, constructing a fully plastic weld interface. This fully plastic interface effectively absorbs and alleviates residual thermal stress caused by the mismatch in thermal expansion coefficients between the ceramic matrix composite and the high-temperature alloy, significantly improving the joint's crack propagation resistance and overall toughness. Therefore, the heterojunction of this application not only possesses high strength and high thermal stability but also excellent sealing performance, meeting the high-reliability connection requirements of hot-end components such as aero-engines.

[0084] The present invention will be further described below with reference to specific embodiments.

[0085] Example 1: Preparation of GH5188 / CMC heterojunction with pre-fabricated sacrificial layer on CMC surface.

[0086] 1. Material and sample preparation (surface treatment) Ceramic Matrix Composites (CMC): SiCf / SiC composites prepared by the precursor infiltration and pyrolysis (PIP) method; High-temperature alloy GH5188: Co-based high-temperature alloy matrix.

[0087] CMC, GH5188, and active brazing filler metal are cut to the required dimensions for metallographic and mechanical testing (the dimensions can be adjusted according to actual needs).

[0088] The surfaces to be joined are sequentially ground and polished and ultrasonically cleaned with acetone for 20 minutes to remove contaminants and improve assembly consistency.

[0089] 2. Preparation of sacrificial layer An organic solution was prepared by dissolving phenol-formaldehyde resin (PF) powder in acetone; the PF mass fraction was 30 wt.%.

[0090] The cleaned CMC sample was placed in a PF solution for vacuum impregnation: the vacuum degree was approximately 0.9 × 10⁻⁶. -1 MPa, impregnation time approximately 15 min, to promote resin penetration into surface micropores / defects.

[0091] After impregnation, curing is carried out at 110 °C for about 1 h in an air atmosphere to form a carbon coating layer.

[0092] Subsequently, the cured sample is subjected to heat treatment in a vacuum brazing furnace: holding at about 800 to 1100 °C for 10 min, so that the carbon coating layer is pyrolyzed and converted into a carbon sacrificial layer.

[0093] 3. Filler Metal Preparation and Assembly The FCC active filler metal alloy is formed by weighing according to the ratio of Cu-20at.%Ni-10at.%Ti, which is prepared by vacuum arc melting, with a melting vacuum of about 5×10 -3 Pa and a current of 500 A, and remelted 8 times to ensure uniform composition. Then, it is cut into sheets (300 in thickness) by methods such as diamond wire sawing / wire cutting. The surfaces to be joined are sequentially ground, polished, and ultrasonically cleaned in acetone for 20 min to remove contaminants and improve assembly consistency.

[0094] 4. Vacuum Brazing Process The assembly is assembled in a sandwich structure and then placed in a vacuum furnace with a vacuum degree of 10 -6 Torr.

[0095] The temperature is raised from room temperature to 1125 °C at a heating rate of 5 °C / min and held for 10 min; subsequently, it is cooled to room temperature at a cooling rate of about 5 °C / min.

[0096] The Scanning Electron Microscope (SEM) image of the GH5188 / CMC heterogeneous joint is as shown in Figure 2 , Figure 2 where (a) is an SEM image with a scale bar of 50 μm, the left side is CMC, the right side is GH5188 superalloy, and the middle is the brazing seam (weld); Figure 2 where (b) is an enlarged view of position b in (a) in Figure 2 , with a scale bar of 20 μm, showing the interface between CMC and the brazing seam. The reaction layer and wetting condition between the active filler metal and CMC can be observed, and points +P1 to +P4 are marked for subsequent Energy Dispersive X-ray Spectroscopy (EDS) composition analysis. Figure 2 where (c) is an enlarged view of position c in (a) in Figure 2 , with a scale bar of 20 μm, showing the microstructure in the middle of the brazing seam. The FCC-based solid solution matrix and a small amount of precipitated phases can be observed, and points +P5 to +P7 are marked for subsequent Energy Dispersive X-ray Spectroscopy (EDS) composition analysis. Figure 2 where (d) is Figure 2The magnified view at point d in (a) shows the interface between the brazing seam and GH5188, with a scale bar of 20 μm. The reaction layer and element diffusion region are visible. Points +P8 to +P11 are marked for subsequent energy dispersive spectroscopy (EDS) analysis. The EDS analysis data for points +P1 to +P11 are shown in Table 1. In Table 1, "-" indicates that the element was not detected.

[0097] Table 1 shows the energy dispersive spectral composition analysis data from +P1 to +P11.

[0098] Figure 2 Image (e) shows the elemental surface distribution of the corresponding junction region obtained by scanning electron microscopy (SEM) coupled with energy-dispersive X-ray spectroscopy (EDS / EDX). Figure 2 As shown in Table 1, Cu is mainly distributed in the brazing seam and is an active brazing filler metal matrix element (CuNiTi). Ni is mainly distributed on the GH5188 side and in the brazing seam, originating from the high-temperature alloy and the active brazing filler metal. Ti is significantly enriched at the interface between CMC and the brazing seam and is an active element. It reacts with SiC in CMC to form reaction layers such as TiC / Ti5Si3. Si mainly comes from the CMC matrix (SiC) and diffuses at the interface. Cr, Co, and W are mainly distributed on the GH5188 side and are the main alloying elements of the high-temperature alloy. C is enriched in CMC and the carbon layer and also reacts with Ti at the interface to form TiC.

[0099] A "sacrificial phase" is pre-placed on the CMC surface. Utilizing the strong reactivity between the sacrificial layer and active elements, an in-situ transformation of the sacrificial layer is achieved, converting it into a barrier layer. Because the barrier layer is formed through reactive transformation, its bonding with the CMC is better than that of the original sacrificial layer. The barrier layer also adheres tightly and densely to the CMC surface, effectively achieving the excessive decomposition of the CMC. The barrier layer can directionally attract active elements such as Ti, V, and Cr from the FCC-based active solder, leaving only FCC structural elements in the weld, thus producing a fully plastic FCC weld.

[0100] Comparative Example 1: Preparation of GH5188 / CMC heterojunction without pre-fabricated sacrificial layer on CMC surface.

[0101] 1. Material and sample preparation (surface treatment) CMC: SiCf / SiC composite material prepared by PIP method; GH5188: Co-based high-temperature alloy matrix.

[0102] CMC, GH5188 and brazing filler metal are cut to the required dimensions for metallographic and mechanical testing (the dimensions can be adjusted according to actual needs).

[0103] The surfaces to be joined are sequentially ground and polished and ultrasonically cleaned with acetone for 20 minutes to remove contaminants and improve assembly consistency.

[0104] 2. Brazing filler metal preparation and assembly The active solder alloy was prepared by vacuum arc melting after weighing according to the ratio of Cu-20at.%Ni-10at.%Ti, with a melting vacuum of approximately 5×10⁻⁶. -3 The material was subjected to a pressure of 500 Pa and a current of 500 A, and remelted eight times to ensure uniform composition. It was then cut into sheets (300 μm thick) using methods such as diamond wire sawing / wire cutting. The surfaces to be joined were sequentially polished and ultrasonically cleaned with acetone for 20 minutes to remove contaminants and improve assembly consistency.

[0105] 3. Vacuum brazing process The assembly is assembled using a sandwich structure and then placed in a vacuum furnace with a vacuum level of approximately 10. -6 Torr.

[0106] The solder was heated from room temperature to 1125 degrees Celsius at a heating rate of approximately 5 °C / min and held at that temperature for 10 min; then cooled to room temperature at a cooling rate of 5 °C / min.

[0107] The scanning electron microscope (SEM) image of the GH5188 / CMC heterojunction is shown below. Figure 3 As shown, a large number of intermetallic compounds (IMCs) are present in the brazing seam. Figure 3 The heterojunction is divided into three zones: Zone I: The GH5188 side interface zone is close to the GH5188 high-temperature alloy. It is mainly a solid solution formed by the mutual dissolution of the brazing filler metal and alloy elements, with a small amount of Cr, Co, W, and other elements diffused from the alloy. The number of IMCs is relatively small. Zone II: The main brazing seam zone is the core area of ​​the weld, formed by the solidification of Cu20Ni10Ti brazing filler metal. Under the condition of no carbon layer, the active element Ti is not effectively consumed, and a large amount of brittle intermetallic compounds (IMCs) such as CuTi and NiTi are precipitated, resulting in complex microstructure and decreased plasticity. This is in stark contrast to the fully plastic FCC weld formed when there is a carbon layer in Example 1. Zone III: The CMC side reaction layer is close to the SiC / SiC CMC. Ti reacts violently with SiC to generate a continuous layer of brittle IMCs such as Ti5Si3 and TiC. Due to the lack of buffering by the carbon layer and the consumption of Ti, this reaction layer is thicker and more brittle, and is prone to becoming a crack initiation point.

[0108] In Comparative Example 1, there is no carbon layer between GH5188 and CMC. Ti reacts directly with CMC and the solder matrix, resulting in a large amount of IMCs precipitating in the weld, significantly increasing the brittleness of the joint and reducing its reliability.

[0109] The strength of the GH5188 / CMC heterojunction without carbon layer in Comparative Example 1 was tested and found to be 43 MPa. The vacuum brazing temperature in step 3 of Comparative Example 1 was raised to 1150 degrees Celsius and held for 10 minutes; the GH5188 / CMC heterojunction cracked, and its strength was 0.

[0110] Example 2 The preparation process of the GH5188 / CMC heterojunction in Example 1 was followed.

[0111] The difference lies in the fact that phenol-formaldehyde resin (PF) powder is dissolved in acetone to prepare an organic solution; the PF mass fractions are 25 wt.%, 35 wt.%, 40 wt.%, and 50 wt.%.

[0112] The strength of multiple GH5188 / CMC heterojunctions prepared in Examples 1 and 3 was tested, and the test results are shown in [the table below]. Figure 4 As the concentration of PF increases, the joint strength shows a trend of "first increasing and then decreasing".

[0113] Example 3 The preparation process of the GH5188 / CMC heterojunction in Example 1 was followed.

[0114] The difference is that in the vacuum brazing process of step 3, the temperature is raised from room temperature to 1100°C, 1150°C, 1175°C and 1200°C respectively at a heating rate of about 5°C / min, and held for 10 min; then cooled to room temperature at a cooling rate of 5°C / min.

[0115] The strength of multiple GH5188 / CMC heterojunctions prepared in Examples 1 and 4 was tested, and the test results are shown in [the table below]. Figure 5 As the brazing temperature increases, the joint strength shows a trend of "first increasing and then decreasing".

[0116] As can be seen, the strength reaches a maximum of 115 MPa under the conditions of 1150 ℃ × 10 min and PF = 30 wt.%. In contrast, the uncoated joint has only 43 MPa at 1125 ℃, and the joint prepared at 1150 ℃ cracked with a strength of 0 MPa. The carbon coating can significantly improve the strength, and under the optimal parameters, the strength is approximately three times that of the uncoated joint.

[0117] While the present invention has been disclosed above, its scope of protection is not limited thereto. Those skilled in the art can make various changes and modifications without departing from the spirit and scope of the present invention, and all such changes and modifications will fall within the scope of protection of the present invention.

Claims

1. A welding method for a ceramic matrix composite / high-temperature alloy dissimilar joint, characterized in that, Includes the following steps: S1: A carbon coating or a boron coating is pre-formed on the welding surface of the ceramic matrix composite material, and the carbon coating or the boron coating is transformed into a carbon sacrificial layer or a boron sacrificial layer by vacuum heat treatment or annealing. S2: Active solder with a face-centered cubic structure as the matrix and the addition of active elements Ti, V or Cr; S3: Assemble the ceramic matrix composite material, the active brazing filler metal, and the high-temperature alloy in a sandwich structure and vacuum weld them. The carbon sacrificial layer or the boron sacrificial layer directionally attracts the active element and reacts with it, thereby transforming the carbon sacrificial layer or the boron sacrificial layer in situ into a carbon barrier layer or a boron barrier layer. This results in the weld seam retaining only a face-centered cubic structure, constructing a fully plastic weld seam interface, and obtaining a ceramic matrix composite material / high-temperature alloy heterojunction.

2. The welding method for ceramic matrix composite / high-temperature alloy dissimilar joints according to claim 1, characterized in that, S1 includes: dissolving phenolic resin in acetone to prepare a phenolic resin organic solution, placing the ceramic matrix composite material in the phenolic resin organic solution for vacuum impregnation, and curing in an air atmosphere to pre-form the carbon coating on the welding surface of the ceramic matrix composite material.

3. The welding method for ceramic matrix composite / high-temperature alloy dissimilar joints according to claim 1, characterized in that, S1 includes: dissolving dopamine powder in alcohol to prepare a dopamine organic solution, spin-coating the dopamine organic solution onto the welding surface of the ceramic matrix composite material, and vacuum drying and curing to achieve the pre-formation of the carbon coating on the welding surface of the ceramic matrix composite material.

4. The welding method for ceramic matrix composite / high-temperature alloy dissimilar joints according to claim 1, characterized in that, S1 includes: performing vacuum heat treatment on the carbon coating at 800°C to 1100°C for more than 10 minutes in a vacuum environment, so that the carbon coating is transformed into the carbon sacrificial layer.

5. The welding method for ceramic matrix composite / high-temperature alloy dissimilar joints according to claim 1, characterized in that, S1 includes: under an inert gas atmosphere, using a boron target to perform radio frequency magnetron sputtering on the welding surface of the ceramic matrix composite material, and sputtering and depositing the boron coating on the welding surface of the ceramic matrix composite material, wherein the thickness of the boron coating is 100 nm to 1 μm.

6. The welding method for ceramic matrix composite / high-temperature alloy dissimilar joints according to claim 1, characterized in that, S1 includes: annealing the boron coating at 150°C to 300°C for 0.5 h to 2 h in a vacuum or inert atmosphere to transform the boron coating into the boron sacrificial layer.

7. The welding method for ceramic matrix composite / high-temperature alloy dissimilar joints according to claim 1, characterized in that, In step S2, the proportion of the active element in the active solder does not exceed 20 at.%, and the active solder is prepared by vacuum arc melting with a melting vacuum of 1×10⁻⁶. -3 Pa to 1×10 -2 Pa, melting current is 450 A to 500 A.

8. The welding method for ceramic matrix composite / high-temperature alloy dissimilar joints according to claim 1, characterized in that, S3 includes: taking the active solder with a particle size D50 of 5 μm to 30 μm and mixing it with terpineol to form a solder slurry; degassing the solder slurry under vacuum; coating it onto the welding surface of the ceramic matrix composite material by scraping or screen printing; drying it under vacuum at 50 ℃ to 80 ℃ and -0.08 MPa to -0.095 MPa for 2 h to 8 h to remove the terpineol; and drying to form a solder interlayer of 50 μm to 300 μm.

9. The welding method for ceramic matrix composite / high-temperature alloy dissimilar joints according to claim 1, characterized in that, S3 includes: heating to the welding temperature range at a heating rate of 3 ℃ / min to 8 ℃ / min and holding at that temperature for 10 min to 30 min to perform the vacuum welding, wherein the welding temperature range is the melting point temperature of the active brazing filler metal plus 50 ℃ to 200 ℃.

10. A ceramic matrix composite / high-temperature alloy heterojunction, characterized in that, It is manufactured using the welding method for ceramic matrix composite / high-temperature alloy heterojunctions as described in any one of claims 1-9.